Extended MSRS rule for seismic analysis of bridges subjected to differential support motions. - Konakli, Katerina (Earthquake engineering & structural dynamics.)
This paper introduces a generalized formulation of the multiple support response spectrum (MSRS) method and extends it by accounting for the quasi-static contributions of truncated modes. The generalized formulation allows consideration of response quantities that involve support degrees of freedom (DOF). This situation arises for many response quantities of interest when rotational DOF are condensed out. New cross-correlation coefficients are introduced in the extended rule and a parametric study is performed to gain insight and identify cases of ground motion spatial variability in which these terms are significant. An efficient computer implementation of the extended MSRS method is described and used for comprehensive analysis of two real bridge models with vastly different structural characteristics. The specified input is in accordance with standards used in engineering practice. The effects of differential support motions, including the influence of spatially varying soil conditions, on the pseudo static and dynamic components and the total response are examined and the improvement achieved with the extended MSRS method is assessed.